THE IMPACT OF PRODUCT AND PROCESS INNOVATIONS ON FINANCIAL RESULTS: АN EMPIRICAL STUDY OF RUSSIAN COMPANIES - O. M. Orlovtseva; E. V. Gubanova (Стратегические решения и риск-менеджмент)
The relationship between product and process innovation and financial performance remains largely unexplored, especially for Russian firms. An analysis of publications on this topic shows both a positive and a negative relationship. At the same time, there are no empirical studies based on Russian companies. This study was conducted on the basis of empirical data from 137 Russian companies. The study shows that investment in R&D has a positive effect on the financial results of the company; and the financial results of the companies depend on the type of innovation (product or process) that the companies carry out.Conducting R&D and scientific research related to product and process innovations can increase the profitability of sales, which characterises the financial results of Russian companies.  In addition, it was concluded that the relationship between process innovations and financial results is stronger than the relationship between product innovations and financial results, which means that it is more profitable to develop and implement process innovations.